The Energy Management System for Lecture Room Through Cooling Method Attendance & Inventory-Based Room Temperature Microcontroller AT89S51 - Mochammad Rifal (Jurnal Sistem Informasi, 2009)
The writing is trying to introduce something of the energy management room cooling system designed aims to regulate the use of energy. This measuring instrument equipped with alarm facility. Alarm Buzzer be useful to know if anyone who came into the room. This measure is based microcontroller AT89S51, where programs written in Assembler programming language. Sensor is used and Phototransistor Sensor LM35 Temperature Sensor, the display uses seven segment two, a Buzzer and Alarm Fan / Motor Drive. LM35 temperature sensor is used to detect the temperature inside the room, if the room temperature reaches the maximum temperature has been determined then the sensor will turn on the fan automatically.